2008
DOI: 10.1007/s11274-007-9643-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the action of the nematophagous fungi Duddingtonia flagrans, Monacrosporium sinense and Pochonia chlamydosporia on Fasciola hepatica eggs

Abstract: This work evaluated the in vitro action of four isolates of the nematophagous fungi Duddingtonia flagrans (AC001), Monacrosporium sinense (SF53) and Pochonia chlamydosporia (VC1 and VC4) on eggs of Fasciola hepatica. The eggs were plated on 2% water-agar with the grown isolates and control without fungus. After 7, 14 and 21 days, the eggs were removed and classified according to the following parameters: effect type 1, lytic effect with no morphological damage to eggshells; type 2, lytic effect with morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 16 publications
0
23
0
2
Order By: Relevance
“…chlamydosporia has proven action against eggs of parasitic nematodes of animals and plants (Lopes et al 2007;Araújo et al 2008). Recent studies, under laboratory conditions, have shown that it can also destroy eggs of trematodes, cestodes and nematodes parasitizing domestic animals (Braga et al 2007(Braga et al , 2008aAraújo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…chlamydosporia has proven action against eggs of parasitic nematodes of animals and plants (Lopes et al 2007;Araújo et al 2008). Recent studies, under laboratory conditions, have shown that it can also destroy eggs of trematodes, cestodes and nematodes parasitizing domestic animals (Braga et al 2007(Braga et al , 2008aAraújo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Nematophagous fungi are classified as endoparasites, predators and parasites of nematode eggs (Araújo et al 2004(Araújo et al , 2008. Pochonia chlamydosporia colonizes and destroys helminth eggs using appressoria developed from undifferentiated hyphae (Braga et al 2007(Braga et al , 2008aAraújo et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…P. chlamydosporia has previously been shown to be ovicidal against eggs of trematodes, cestodes and nematodes in vitro under laboratories conditions (Araujo et al, 2009;Braga et al, 2007Braga et al, , 2008, however, this is the first report of its ovicidal activity against eggs of D. renale. The production of chlamydospores, resistant structure, is one of the main characteristics of a fungus, which possibly could be used in environmental control of Biocontrol Science and Technology 403 parasitic gastrointestinal helminth eggs (Braga et al, 2007).…”
Section: Discussionmentioning
confidence: 74%
“…This might be due to that the isolates had lytic effect on the eggs wall without morphological damage. In this sense, Braga et al [20] found that the fungi Duddingtonia flagrans and Monacrosporium sinense had shown lytic effect on F. hepatica egg wall without its morphological damage reached 66.5 and 73.4%, respectively. Also, the same author reported the same effect on eggs of Ascris lumbricoides.…”
Section: Discussionmentioning
confidence: 99%
“…At present, effective and commercial vaccines are not yet available; therefore anthelmintic drugs are the main method employed for controlling the fluke infection [19]. However, due to emergence of resistance and the cost of animal treatment, especially for small ruminants, the use of new control alternative measures is important, especially of the present eggs in the pasture, such as biological control [20]. The use of bacteria appears therefore as a viable and promising control alternative for constantly infected animals.…”
Section: Introductionmentioning
confidence: 99%